(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Futsal as leisure time sport is very popular in Indonesia. However, this sport is characterized by high intensity which tends to cause dehydration. Aim: The aim of this study was to identify pre-exercise hydration status of recreational futsal players and develop information media to prevent dehydration in Indonesia recreational futsal players. Method: Descriptive cross-sectional study was implemented as part of preliminary study to get the picture of pre-exercise hydration status of recreational futsal players. Twenty seven male participants were recruited in this study (age 22 + 3.19 years old., weight 65.85 + 13.54 kg, height 1.69 + 0.08 m, BMI 22.73 + 3.08 kg/m2). Hydration status was checked by using urine strip test before they played futsal. Participants filled out short questionnaires to find out the information source of dehydration. Information media was created based on the result of this preliminary study to prevent dehydration. Additionally, media expert and sports medicine doctor also assessed the development of information media. Result: The preliminary study showed that 77.7% (n = 21) of the subjects suffered from dehydration before playing futsal. The short questionnaires result showed that most of the subjects received information about dehydration from television (52%) and internet (43%). The content and design of developed information media was considered valid by the experts. Conclusion: Our findings conclude that incidence of pre-exercise dehydration among recreational futsal players in Indonesia was high. Further study to evaluate the use of developed information media is needed to prevent the risk of dehydration during high intensity exercise. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.122-128